Lead-Free Soldering - Bath, Jasbir.; Bath, Jasbir. (Springer US : Imprint: Springer, 2007)
The push toward lead-free soldering in computers, cell phones and other electronic and electrical devices has taken on a greater urgency as laws have been passed or are pending in the United States, the European Union and Asia which ban lead-bearing solder. These new restrictions on hazardous substances are changing the way electronic devices are assembled, and specifically affect process engineering, manufacturing and quality assurance. Lead-Free Soldering offers in a single volume a broad collection of practical techniques for lead-free soldering design and manufacture, which up to now have been scattered in difficult-to-find scholarly sources. The book includes the latest information on proposed changes to lead-free standards, and up-to-date analysis of government and legislative activities and regulations in North America, Europe and Asia. Written by recognized experts in both academia and industry, Lead-Free Soldering is a must-have guide for practicing engineers interested in the latest developments surrounding areas such as lead-free alloy properties, reflow, wave, rework , solder joint reliability, PCB laminates and surface finishes, and backward and forward compatibility.